2002
DOI: 10.1093/cercor/12.7.772
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Substrates of Biological Motion Perception: an fMRI Study

Abstract: We used fMRI to identify the brain areas related to the perception of biological motion (4 T EPI; whole brain). In experiment 1, 10 subjects viewed biological motion (a human figure jumping up and down, composed of 21 dots), alternating with a control stimulus created by applying autoregressive models to the biological motion stimulus (such that the dots' speeds and amplitudes were preserved whereas their linking structure was not). The lengths of the stimulus bouts varied, and therefore the transitions betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
80
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 45 publications
14
80
0
3
Order By: Relevance
“…Such a discrimination of static displays would be based purely on geometrical cues and is clearly different from the discrimination based on the percept of a walking human figure which is only evoked by animated displays of biological motion. Moreover, we found sources of the ERP signal in the second component in brain areas which were reported to be selectively involved in biological motion perception in several imaging studies [11,[24][25][26][27]51,62] but were not reported to be activated by static displays consisting of a few dots which match joint positions.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Such a discrimination of static displays would be based purely on geometrical cues and is clearly different from the discrimination based on the percept of a walking human figure which is only evoked by animated displays of biological motion. Moreover, we found sources of the ERP signal in the second component in brain areas which were reported to be selectively involved in biological motion perception in several imaging studies [11,[24][25][26][27]51,62] but were not reported to be activated by static displays consisting of a few dots which match joint positions.…”
Section: Discussionmentioning
confidence: 78%
“…The ANOVAs were conducted for the factors stimulus category (BM versus inverted BM versus scrambled motion), selected electrode locations (O1, O2 versus PO7, PO8 versus P7, P8 versus TP7, TP8) and recording side (right versus left). Electrode selection was based on the main areas of interest as suggested by previous functional imaging studies [11,[24][25][26][27]51,62]. Greenhouse-Geisser adjustments to the degrees of freedom were performed when appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The STS is more activated when subjects selectively attend to eye gaze than to face identity [1,2,9]. Regions in the STS also respond to a range of visual signals salient for social interaction, such as mutual gaze, emotional expression, speech, intentional limb movements, and biological motion in general [1,2,9,[36][37][38][39]. Grossman et al (2005) suggested that normal STS functioning is required for perception of biological motion, as repeated transcranial magnetic stimulation (rTMS) disrupted cortical activity in the posterior STS and reduced perceptual sensitivity to point-light animations in healthy adults [36].…”
Section: The Neural Basis Of Gaze Processing: the Role Of Stsmentioning
confidence: 99%